Implementation of policy and management interventions to improve health and care workforce capacity to address the COVID-19 pandemic response: a systematic review - Ana Paula Cavalcante de Oliveira; Mariana Lopes Galante; Leila Senna Maia; Isabel Craveiro; Alessandra Pereira da Silva; Ines Fronteira; Raphael Chança; Giorgio Cometto; Paulo Ferrinho; Mario Dal Poz (Human Resources for Health, 2023)
Abstract Background The COVID-19 pandemic highlighted pre-existing weaknesses in health and care systems and services and shortages of health and care workers (HCWs). As a result, policymakers needed to adopt measures to improve the health and care workforce (HCWF) capacity. This review aims to identify countries’ range of policies and management interventions implemented to improve HCWs’ capacity to address the COVID-19 pandemic response, synthesize their evidence on effectiveness, and identify gaps in the evidence. Methods The literature was searched in PubMed, Embase, Scopus, LILACS–BVS, WHO’s COVID-19 Research Database and the ILO, OECD and HSRM websites for literature and documents published between January 2020 and March 2022. Eligibility criteria were HCWs as participants and policy and management interventions aiming to improve HCWF capacity to address the COVID-19 pandemic response. Risk of bias was assessed with Joanna Briggs Institute (JBI) Critical Appraisal Tools (CAT) and certainty of the evidence in presented outcomes with GRADE. Results The searches retrieved 3378 documents. A total of 69 were included, but only 8 presented outcomes of interventions implemented. Most of the selected documents described at least one intervention implemented by countries at the organizational environment level to increase the flexibility and capacity of the HCWF to respond to the pandemic, followed by interventions to attract and retain HCWs in safe and decent working environments. There was a lack of studies addressing social protection, human resources for health information systems, and regarding the role of community health workers and other community-based providers. Regarding the risk of bias, most of documents were rated as medium or high quality (JBI’s CAT), while the evidence presented for the outcomes of interventions was classified as mostly low-certainty evidence (GRADE). Conclusions Countries have implemented various interventions, some innovative, in response to the pandemic, and others had their processes started earlier and accelerated by the pandemic. The evidence regarding the impact and efficacy of the strategies used by countries during the pandemic still requires further research.